Cervical morbidity in Alsace, France: results from a regional organized cervical cancer screening program. Issue 1 (January 2019) - Baldauf, Jean-Jacques; Fender, Muriel; Bergeron, Christine; Marrer, Emilie; Velten, Michel; Pradat, Pierre; Arbyn, Marc
Abstract : In 1994, a pilot program of cervical cancer screening was introduced in the Alsace region, France. Women aged 25–65 years were proposed to have one Pap smear every 3 years. The objective was to assess cervical morbidity in Alsace before the human papillomavirus vaccinated population reaches the age of screening. Data on cervical lesions and cancers were collected by EVE for the period September 2008 to August 2011 from existing medical services and cytopathology laboratories in Alsace. Cytological and histological data were completed with data from the two cancer registries covering the region (Bas-Rhin and Haut-Rhin). Cancer incidence rates were computed for the target population (truncated to 25–64 years) and were age standardized according to the world reference population. World standardized incidence rates for the whole female population were obtained from the two cancer registries. During 2008–2011, 565 153 smears were performed in 498 913 women aged 25–64 years, representing an average of 1.13 smears/woman and 1.62 smears/screened woman. The overall screening coverage was 70.1% over the 3-year period. Histologically confirmed high-grade lesions were found in 2303 women (0.5%). Moreover, 215 cervical cancers were reported among women aged 25–64 years (crude and standardized truncated incidence rate of 10.6 and 10.0/100 000 women-years, respectively). The overall screening coverage of 70% at 3 years is higher than the national rate (57%), and the overall cancer incidence of 5.5/100 000 is below the national French level. The EVE database will be useful to assess trends in cervical morbidity over time and to further assess the effect of screening as well as of human papillomavirus vaccination. Abstract : Supplemental Digital Content is available in the text.